Analisis Kelaikan Fungsi Jalan Menggunakan Metode AHP dan Maut pada Ruas Jalan A.H. Nasution (Medan) dan Jalan Ngumban Surbakti (Medan) - Ahmad Arifin Porkas Lubis; Ahmad Perwira Mulia; Gina Cynthia Raphita Hasibuan (Jurnal Syntax Admiration, 2023)
Road infrastructure is an important aspect in supporting economic growth and human mobility. Good and safe road conditions will increase the effectiveness and efficiency of transportation. However, in reality, some road sections still do not meet fairly strict standards, both in terms of feasibility and safety. The roads of A.H. Nasution (Medan) and Ngumban Surbakti (Medan) have never undergone a feasibility test before. Therefore, in this study a ranking will be formed to determine the level of feasibility of the function of both. This study was conducted to evaluate the feasibility of A.H. Nasution (Medan) and Ngumban Surbakti (Medan) roads using the AHP (Analytical Hierarchy Process) method and the MAUT (Multi-Attribute Utility Theory) method. The data that has been collected will be processed and analyzed using the AHP and MAUT methods. The AHP method and the MAUT method are used to determine the relative weight of each of the factors affecting roadworthiness. Assessment of respondent data using the AHP method obtained the largest weight on road technical by 3.36 on the A.H. Nasution road section and 3.04 on the Ngumban Surbakti road section. While the smallest weight on technical road equipment is 0.592 on the A.H. Nasution road section and the utilization of the road section is 0.3 on the Ngumban Surbakti road section. The assessment of respondents' data using the MAUT method obtained the largest weight on road complementary building structures of 1,265 on the A.H. Nasution road section and 1,140 on the Ngumban Surbakti road section. While the smallest weight on the utilization of road sections is 0.04 on the A.H. Nasution road section and 0.413 on the Ngumban Surbakti road section.